Asymmetric N-heterocyclic carbene (NHC)-catalyzed annulation of modified enals with enolizable aldehydes - Yetra, Santhivardhana Reddy; Kaicharla, Trinadh; Kunte, Sunita S.; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2013)
N-Heterocyclic carbene (NHC)-catalyzed highly enantioselective lactonization of modified enals with enolizable aldehydes, proceeding via the alpha,beta-unsaturated acylazolium intermediates, is reported. The reaction results in the asymmetric synthesis of synthetically important 4,5-disubstituted dihydropyranones.

Aryne [2,3] stevens rearrangement - Roy, Tony; Thangaraj, Manikandan; Kaicharla, Trinadh; Kamath, Rupa V.; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2016)
Arynes are employed in the transition-metal-free and mild [2,3] Stevens rearrangement of tertiary allylic amines for the synthesis of functionalized homoallylic amines in moderate to good yield with a broad substrate scope. The key nitrogen ylide intermediate was generated by the N-arylation of allyl amines using arynes. Moreover, the reaction of chiral allyl amines with arynes resulted in the enantiospecific synthesis of homoallylic amines. In addition, preliminary studies on the [1,2] Stevens rearrangement is also presented.

AgOTf-catalyzed dehydrative [3+2] annulation of aziridines with 2-naphthols - Kaicharla, Trinadh; Jacob, Anu; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2017)
The reaction of 2-naphthols with aziridines in the presence of AgOTf resulting in a dehydrative, formal [3+2] annulation is reported. The reaction allows the synthesis of functionalized benzoindolines, and tolerates a broad range of functional groups. A preliminary study on themechanism of this reaction indicates an SN1-type ring-opening of aziridines. This method is demonstrated for the one-pot synthesis of benzoindoles.